2017
DOI: 10.1097/inf.0000000000001387
|View full text |Cite
|
Sign up to set email alerts
|

Growth at 2 Years of Age in HIV-exposed Uninfected Children in the United States by Trimester of Maternal Antiretroviral Initiation

Abstract: Background Abnormal childhood growth may affect future health. Maternal tenofovir (TFV) use was associated with lower body length and head circumference at one year of age in HIV-exposed uninfected (HEU) US children. Methods We studied 509 HEU children in the US-based Surveillance Monitoring of ART Toxicities cohort whose HIV-infected mothers were not using antiretrovirals at the last menstrual period and began combination antiretroviral therapy (cART) in pregnancy (cART-initiators). We examined adjusted ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Additional data on infant safety (including bone growth) from studies of pregnant women receiving antiretroviral therapy found no increase in adverse events among TDF-exposed versus unexposed infants. (71)(72)(73) Although a previous study of HIV-infected pregnant mothers found TDFexposed infants to have 12% lower whole-body bone mineral content than unexposed infants, (74) the followup study showed no differences at 2 years of age. (71) Whether invasive procedures during pregnancy, such as amniocentesis, increase the risk of HBV infection in the infants is unclear.…”
Section: C Counseling Of Hbsag-positive Women In Pregnancy and Postmentioning
confidence: 84%
See 2 more Smart Citations
“…Additional data on infant safety (including bone growth) from studies of pregnant women receiving antiretroviral therapy found no increase in adverse events among TDF-exposed versus unexposed infants. (71)(72)(73) Although a previous study of HIV-infected pregnant mothers found TDFexposed infants to have 12% lower whole-body bone mineral content than unexposed infants, (74) the followup study showed no differences at 2 years of age. (71) Whether invasive procedures during pregnancy, such as amniocentesis, increase the risk of HBV infection in the infants is unclear.…”
Section: C Counseling Of Hbsag-positive Women In Pregnancy and Postmentioning
confidence: 84%
“…(71)(72)(73) Although a previous study of HIV-infected pregnant mothers found TDFexposed infants to have 12% lower whole-body bone mineral content than unexposed infants, (74) the followup study showed no differences at 2 years of age. (71) Whether invasive procedures during pregnancy, such as amniocentesis, increase the risk of HBV infection in the infants is unclear. Two studies including 21 and 47 HBsAg mother-infant pairs respectively concluded that the risk of HBV transmission by amniocentesis is low.…”
Section: C Counseling Of Hbsag-positive Women In Pregnancy and Postmentioning
confidence: 84%
See 1 more Smart Citation
“…Teratogenic effects of antiviral therapy during pregnancy have not been demonstrated. One study showed that exposure to TDF during pregnancy led to a 12% decrease in bone mineralization in exposed children after birth [78], but this difference had completely disappeared at the age of 2 [79]. No transmission was demonstrated in studies where highly viremic women received antiviral therapy during the last trimester, and where the children were vaccinated and received HBIG soon after childbirth [80,81].…”
Section: Pregnancy and Childbirthmentioning
confidence: 99%
“…LactMed does not advise against breastfeeding with either LAM or tenofovir, given minimal drug exposure in nursing infants. Although concern for bone toxicity has been raised with infants exposed to TDF, there appear to be no differences in bone growth at 2 years of infant follow‐up . Data on TBV safety in breastfeeding remain limited, further supporting use of alternate antivirals in pregnant and postpartum women meeting HBV treatment indications.…”
Section: Hepatitis B Treatment During Pregnancymentioning
confidence: 99%